STRATEGI PENGENDALIAN PERSEDIAAN LOGISTIK DALAM MENDUKUNG MUTU LAYANAN KEFARMASIAN DI FASILITAS KESEHATAN - Irfan Kurniawan; Azahratul Jannah; Salwah Suardi; Rezki Ramdani (Jurnal Manajemen Kesehatan Indonesia, 2026)
Health logistics inventory control is an essential component of pharmacy management to ensure medicine availability and support the continuity of pharmaceutical services. Inventory management that is not systematically planned may result in stockouts or excess inventory. This study aimed to describe the implementation of health logistics inventory control at PPKG Pharmacy in Makassar City using a combination of ABC analysis, Economic Order Quantity (EOQ), Reorder Point (ROP), and Safety Stock (SS) methods. This study employed a descriptive quantitative design with a retrospective approach. The data were obtained from records of health logistics availability and utilization from January to December 2024, as well as interviews with pharmaceutical personnel regarding the inventory control system. ABC analysis was used to classify items based on their value contribution to usage, EOQ to calculate economically planned order quantities, ROP to determine reorder points, and SS to establish buffer stock levels. The results indicate that ABC analysis effectively identifies priority items requiring stricter monitoring, while the application of EOQ, ROP, and SS provides a systematic basis for planning the quantity and timing of medicine orders. Based on these findings, it is recommended that PPKG Pharmacy consider implementing the integrated ABC–EOQ–ROP–SS methods within its inventory management system as a decision-support alternative for procurement planning and stock monitoring, in order to minimize the risks of stockouts and overstocking and to support the sustainability of pharmaceutical services. Keywords: Inventory Management, ABC Analysis, Economic Order Quantity (EOQ), Reorder Point (ROP), Safety Stock; Pharmacy.